تحليل الأخطاء الإملائية لهمزة القطع والوصل في مهارة الكتابة لطلبة المدرسة المتوسطة الإسلامية الحكومية السادسة تولونج اغونج - Laela, Alif; Daroini, Slamet (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
ملخص في اللغة العربية توجد أربع مهارات اللغوية ، وهي الاستماع والكلام والقراءة والكتابة. لتكون قادرا على إتقان مهارة الكتابة يجب أن يفهم كيفية الكتابة الصحيحة من ناحية الإملاء. ولكن في الواقع لا تزال الأخطاء الكثيرة في مهارة الكتابة، بما في ذلك في كتابة الهمزة. بحثت الباحثة الأخطاء التي تحدث في مهارة الكتابة خاصة في همزة القطع والوصل. أهداف هذا البحث لمعرفة أشكال أخطاء الإملائية في كتابة الهمزة القطع والوصل. استخدمت الباحثة المدخل الكيفي الوصفي. وأمّا طريقة جمع البيانات هي المقابلة والوثائق. وكان تحليل البيانات في هذا البحث تتكون من (1) معرفة الأخطاء. (2) وصف الأخطاء. (3) الاستخلاص. واستخدمت الباحثة فحص صحة البيانات بطريقة التثليث. نتائج من هذا البحث يعني توجد الأخطاء في كتابة همزة القطع منها في أول الكلمة وفي أخير الكلمة. وأنواع الأخطاء في همزة القطع منها وقع في الاسم والفعل والحروف. أمّا توجد أخطاء في كتابة همزة الوصل منها في أول الكلمة وأخطاء الكتابة في وسط الكلمة. وأنواع الأخطاء في همزة الوصل منها وقع في فعل الماضي ، والأمر ، ومصدر. ABSTRACT In Arabic, there are four language skills, namely listening skill, speaking skill, reading skill, and writing skill. For students to be able to master the skill of writing they must understand how to write correctly in terms of writting. However, in fact, many errors are still found in the writing skills including in the writing of the hamza. This study discusses the errors that occur in writing skills especially in hamza qatha and washal. The objectives of this study are: To find out the types of writing errors in writing hamza qatha' and washal. Researchers use descriptive qualitative methods. Data collection techniques used are interviews and documentation. Data analysis in this study consisted of three stages including (1) Recognizing errors. (2) Describe the error. (3) Drawing conclusions. Meanwhile to test the validity of the data researchers used a triangulation technique. The results of this study are: (1) There are errors in writing hamzah qatha' at the beginning of words and writing errors at the end of words. Various kinds of mistakes in hamza qatha' include the noun, verb, and conjunctions. Meanwhile, the writing errors of hamza washal are found at the beginning of the word and writing errors in the middle of the word. The various mistakes of the hamza washal include past tense, command verb, and masdar.